IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY BERDASARKAN KONSEP TRIPLE BOTTOM LINE PT BANK SYARIAH XYZ TAHUN 2018, 2019 dan Q3 2020 - Fajar Ardhiansyah; Pramelani pramelani (Jurnal Ekonomi dan Bisnis (EK&BI), 2021)
Companies in enhancing a good image or image need social thinking which is not only concerned with seeking profit only in the business world. All social activities are carried out by corporate social responsibility. Therefore this research was conducted to determine the implementation of corporate social responsibility (CSR) carried out by PT Bank Syariah XYZ. The sample of this research is the financial performance report of PT Bank Syariah XYZ using quantitative research and data analysis techniques using the measurement of the Triple Bottom Line concept of PT Bank Syariah XYZ in 2018, 2019 and Q3 2020 with the EVA (Economic Value Added) method. The results obtained from this study are that the EVA number always has a positive tendency or is greater than zero, as a result it proves that CSR activities have an influence on Value added for entrepreneurs. The results of this triple bottom line measurement have been tested to be able to assess whether or not there is an EVA from the CSR of PT Bank Syariah XYZ which produces benefits from year to year. XYZ Syariah Bank annually throughout 2017– 3rd quarter 2020. Keywords: Corporate Social Resposibility, Triple Bottom Line, Economic Value Added